Learners Engagement in Online Teacher Professional Development: Scale Development and Validation - Johanes L. Taloko; Sri Rachmajanti; Francisca Maria Ivone (JEELS (Journal of English Education and Linguistics Studies), 2024)
Research has shown that effective online teacher professional development (OTPD) requires teachers to learn and engage professionally to become high-quality teachers. Understanding teachers' engagement as learners in OTPD is crucial as such engagement indicates active learning, interaction, and collaboration with other teachers. Nevertheless, there has not been any instrument measuring how teachers behave (behavioral), feel (emotional), think (cognitive), and socialize (social). Therefore, the goal of the present study was to create a context-specific survey instrument to measure the engagement of EFL teachers in OTPD. This study, using the research and development (R&D) method,   involved 385 Indonesian in-service EFL teachers in nine universities conducting OTPD in Indonesia. The statistical results of explanatory (EFA) and confirmatory factor analyses (CFA) confirmed the four-dimensional construct in the OTPD Learner Engagement Instrument, mainly behavioral, emotional, cognitive, and social dimensions of engagement. The study's policy and practical implications addressing the policymakers, institutions, and future research were also presented.